2021
DOI: 10.18203/2320-6012.ijrms20210410
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic findings in COVID-19 patients

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS CoV2) has caused the global pandemic, COVID-19. Though predominantly a respiratory illness, cardiac manifestations of COVID-19 significantly contribute to mortality. We wanted to determine whether admission electrocardiographic (ECG) characteristics provide prognostic information in COVID-19.Methods: We performed a retrospective, cross-sectional observational study in a designated District COVID hospital. COVID-19 patient’s medical records were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…The electrocardiogram may show ST segment elevation or depression, T-wave depression, bidirectional or inverted changes after COVID-19. ST segment elevation can be seen in myocarditis or pericarditis, while ST segment depression and T-wave changes can be seen in myocardial ischemia, which may be caused by obstructive coronary artery disease or oxygen supply-demand imbalance [20,21]. A meta-analyse is showed that up to 40% of COVID-19 patients from different hospitals worldwide experience ST-T changes, some of which are accompanied by elevated troponin levels.…”
Section: Discussionmentioning
confidence: 99%
“…The electrocardiogram may show ST segment elevation or depression, T-wave depression, bidirectional or inverted changes after COVID-19. ST segment elevation can be seen in myocarditis or pericarditis, while ST segment depression and T-wave changes can be seen in myocardial ischemia, which may be caused by obstructive coronary artery disease or oxygen supply-demand imbalance [20,21]. A meta-analyse is showed that up to 40% of COVID-19 patients from different hospitals worldwide experience ST-T changes, some of which are accompanied by elevated troponin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Patients infected with SARS-CoV-2 who associate myocardial injury may show ST-segment elevation, ST-segment depression, or T-wave inversion on ECG [ 18 , 19 ]. Howbeit, the ST-segment elevation in COVID-19 patients requires differential diagnosis with pericarditis and myocarditis, while myocardial ischemia may be due to both obstructive coronary artery diseases and a mismatch between oxygen supply and demand [ 88 ]; these findings have been observed more frequently in severe patients [ 13 , 22 ]. Among the critically ill patients, an abnormal ECG with ST-T changes reaches a frequency of 48.5%, while in patients with a severe type of COVID-19, 25.7% have this abnormality according to Wang et al [ 89 ].…”
Section: Electrocardiographic Changes In Myocardial Ischemia In Covid...mentioning
confidence: 99%
“…Most studies found that ST-T abnormalities were the most common changes, occurring in up to 40% of patients from different hospitals, including Wuhan Asia General Hospital [ 15 , 19 , 88 , 90 ]. T-wave inversion was the most common repolarization change in several studies, including the one of Galidevara et al, who reported that 27.7% of ECG changes were due to this abnormality [ 7 , 22 ]. However, while Rosen et al reported in his study that 21% patients had an ECG with ST-T modification, Poterucha et al reported that 10% of the presentations had this abnormality, T-wave inversion was observed in up to 29% of this group, which is similar to other studies.…”
Section: Electrocardiographic Changes In Myocardial Ischemia In Covid...mentioning
confidence: 99%
See 2 more Smart Citations